Cancer incidence and death rates in Argentine rural towns surrounded by pesticide-treated agricultural land - Damián Verzeñassi; Alejandro Vallini; Facundo Fernández; Lisandro Ferrazini; Marianela Lasagna; Anahí J. Sosa; Guillermo E. Hough (Elsevier, 2023)
Background: A number of published reports have linked agricultural pesticides (AP) to different illnesses, one of which is cancer. Our objectives were to estimate cancer incidence and death rates in small Argentine rural towns affected by AP; and to compare these estimations with indexes from Argentina's general population. Methodology: An epidemiologic house-to-house health survey conducted by last-year medical students was implemented in 8 small rural towns of the Province of Santa Fe- Argentina (8 T), each surrounded by fields sprayed with AP. The survey covered 27,644 people, accounting for 68% of the total 8 T population. Results: Odd-ratio between cancer incidence rate in 8 T and the general population was 1.37 (P<5%). For the 15-44 year age-group, odd-ratios between cancer death rates per 100 thousand inhabitants in 8 T and the general population were 2.48 and 2.77 for female and male genders, respectively. Proportion of cancer-deaths in relation to other causes of death varied by age-group and gender, 8 T values were higher than for the general population for all combinations. Conclusions: Our findings suggest that living in small rural towns affected by nearby AP applications has a negative health impact, namely in cancer outcomes. These results contribute to the need for pesticide-reduction policies, especially in the surroundings of small urban populations.